TILLER PROPAGATION OF CERRADO GRAMINOIDS: NEW POSSIBILITIES FOR SEEDLING PRODUCTION (SCIENTIFIC NOTE) - Lucas Dias Sanglade; Raquel Stucchi Boschi; Gabriela Strozzi; Dalva Maria da Silva Matos; Vânia Regina Pivello (Revista do Instituto Florestal)
The lack of knowledge and ecological challenges in the reproduction of Cerrado graminoids has prevent the commercial production of native seedling, complicating efforts to restore the Cerrado. This study aimed to assess the survival of vegetative tillers from clonal propagation of five native caespitose graminoid species from the Cerrado. We collected ten adult plants (matrices) per species in of a cerrado sensu stricto area, located at São Carlos – SP, to be used as source of clonal units (tillers). A total of 68 tillers per specie were separated and transplanted into containers, with survival monitored under nursery conditions for 60 days. Axonopus pellitus, Bulbostylis hirtella and Aristida jubata showed survival rates close to 70%, while Aristida setifolia and Andropogon bicornis had survival rates below 12%. These results suggest that tiller transplanting could be a viable method for commercial production of certain Cerrado graminoids, contributing to the of this biome.